First molecular characterization of Giardia duodenalis from goats in Malaysia - Lim, Yvonne A. L.; Mahdy, Mohammed A. K.; Tan, Tiong Kai; Goh, Xiang Ting; Jex, Aaron R.; Nolan, Matthew J.; Kumar Sharma, Reuben Sunil; Gasser, Robin B. (Elsevier, 2013)
In the present study, 310 faecal samples from goats from eight different farms in Malaysia were tested for the presence of Giardia using a PCR-coupled approach. The nested PCR for SSU amplified products of the expected size (∼200 bp) from 21 of 310 (6.8%) samples. Sixteen of these 21 products could be sequenced successfully and represented six distinct sequence types. Phylogenetic analysis of the SSU sequence data using Bayesian Inference (BI) identified Giardia assemblages A, B and E. The identification of the ‘zoonotic’ assemblages A and B suggests that Giardia-infected goats represent a possible reservoir for human giardiasis in Malaysia.